2005
DOI: 10.1002/ana.20424
|View full text |Cite
|
Sign up to set email alerts
|

Age at onset variance analysis in spinocerebellar ataxias: A study in a Dutch–French cohort

Abstract: In dominant spinocerebellar ataxias (SCAs), the issue of whether non-CAG dependent factors contribute to onset age remains unsettled. Data on SCA genotype, onset age, normal/expanded CAG repeat length, sex of the patient and transmitting parent, and family details were available from 802 patients. Based on the model [log(10) (age at onset) = k - b CAG(exp) + epsilon], we examined changes in adjusted R(2) and residual standard error following incorporation of the other factors in this model. The expanded repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
4
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 34 publications
7
86
4
2
Order By: Relevance
“…For example, individuals with a glutamine repeat of 20 begin to exhibit symptoms in their 70s, while individuals with a repeat length of 30 glutamines begin to exhibit symptoms as early as 30 years old. 12 The findings of the SCA6 mutation in humans and the spontaneous mouse mutant leaner Cterminal ␣1A splice mutation strongly suggest that genetic mutation of the C-terminus has significant functional consequences.…”
Section: Cacna1a Geneticsmentioning
confidence: 99%
“…For example, individuals with a glutamine repeat of 20 begin to exhibit symptoms in their 70s, while individuals with a repeat length of 30 glutamines begin to exhibit symptoms as early as 30 years old. 12 The findings of the SCA6 mutation in humans and the spontaneous mouse mutant leaner Cterminal ␣1A splice mutation strongly suggest that genetic mutation of the C-terminus has significant functional consequences.…”
Section: Cacna1a Geneticsmentioning
confidence: 99%
“…The Genetic Modifiers of Huntington's Disease (GeM‐HD) genome‐wide association study (GWAS)6 found two genome‐wide loci associated with age at motor onset in HD on chromosomes 15 and 8, with two independent signals at the same locus on chromosome 15. A few SCA genetic modifiers have been proposed3, 5, 7, 8, 9 and no GWAS have been reported.…”
mentioning
confidence: 99%
“…The reported incompleteness of the genotype-phenotype correlation, observed in MJD as well as in other SCAs, confirms the involvement of non-CAG factors in the explanation of the phenotype, that can either be genetic or environmental (van de Warrenburg et al, 2005). For MJD, the hypothesis that an important fraction of the residual of the disease onset (after accounting for the CAG repeat size) is of genetic nature has been reinforced (DeStefano et al, 1996;van de Warrenburg et al, 2005).…”
Section: Clinical Variabilitymentioning
confidence: 92%
“…For MJD, the hypothesis that an important fraction of the residual of the disease onset (after accounting for the CAG repeat size) is of genetic nature has been reinforced (DeStefano et al, 1996;van de Warrenburg et al, 2005). The few studies that attempted to identify MJD modifiers have used candidate gene approaches; Jardim et al (2003), in a study that considers the effect of the CAG tract at several expansion loci (namely SCA2, SCA6 and DRPLA), only found a correlation between the severity of fasciculations and the size of the CAG tract at the SCA2 locus.…”
Section: Clinical Variabilitymentioning
confidence: 99%